TINJAUAN HUKUM ISLAM TERHADAP AKAD NIKAH MELALUI TELEPON (STUDI KASUS PADA KELURAHAN LAMOKATO, KEC. KOLAKA, KAB. KOLAKA) - Muh. Imran umar; Muhammad Yusuf Nasir; Akmir Akmir (IAI Al-Mawaddah Warrahmah Kolaka, 2022)
Islamic law is a set of regulations based on Allah's revelation and the sunnah of the Prophet regarding the behavior of mukhallaf humans which are recognized and believed to be binding for all who are Muslims. Islamic law is universal. Law must develop according to the social needs of the community, as the rule in fiqh that